THE ROLE OF INVESTMENT IN THE DEVELOPMENT OF THE NATIONAL ECONOMY - Sharipov Boburbek Batiralevich (International Engineering Journal For Research & Development, 2020)
This article provides information on the role and place of investment in the development of the economy of the Republic of Uzbekistan and develops a number of scientific proposals to improve the industry